Β-Blockers in sepsis: protocol for a systematic review and meta-analysis of randomised control trials. Issue 6 (23rd June 2016) - Duan, Erick H; Oczkowski, Simon J W; Belley-Cote, Emilie; Whitlock, Richard; Lamontagne, Francois; Devereaux, Phillip J; Cook, Deborah J
Abstract : Introduction: Sepsis is a common and deadly complication of infection. As part of the host response, sympathetic stimulation can result in septic myocardial depression, and metabolic, haematological and immunological dysfunction. Administration of β-blockers may attenuate this pathophysiological response to infection, but the effects on clinical outcomes are unknown. The objective of this systematic review is to determine the efficacy and safety of β-blockers in adults with sepsis using data from randomised control trials. Methods and analysis: We will identify randomised control trials comparing treatment with β-blockers, versus placebo or standard care in adults with sepsis. Data sources will include MEDLINE, EMBASE, CENTRAL, clinical trial registries and conference proceedings. Two reviewers will independently determine trial eligibility. For each included trial, we will conduct duplicate independent data extraction, risk of bias assessment and evaluation of the quality of the evidence using the GRADE approach. Ethics and dissemination: Our systematic review will evaluate the effects of β-blockers in adults with sepsis, comprehensively summarising and appraising the available evidence from randomised control trials. The results of this systematic review will help clinicians treating patients with sepsis to understand the potential role of β-blockade, and inform future research on this topic. Our findings will be disseminated through conference presentation and publication in a peer-reviewed journal. Trial registration number: CRD42016036933.